Rice Sucrose Partitioning Mediated by a Putative Pectin Methyltransferase and Homogalacturonan Methylesterification. Issue 3 (11th May 2017) - Xu, Yonghan; Sechet, Julien; Wu, Yingbao; Fu, Yaping; Zhu, Longfei; Li, Jincai; Zhang, Yinping; Gineau, Emilie; Gaertner, Cyril; Zhou, Jian; Fan, Xiaorong; Liu, Yu; et al.
Abstract : OsQUA2 is necessary for high-HG methylesterification in the rice culm sieve element cell wall to facilitate source-to-sink sucrose allocation by ensuring the normal long-distance inter-SE movement of sucrose. Abstract: Homogalacturonan (HG ) is the main component of pectins. HG methylesterification has recently emerged as a key determinant controlling cell attachment, organ formation, and phyllotaxy. However, whether and how HG methylesterification affects intercellular metabolite transport has rarely been reported. Here, we identified and characterized knockout mutants of the rice ( Oryza sativa ) OsQUA2 gene encoding a putative pectin methyltransferase. Osqua2 mutants exhibit a remarkable decrease in the degree of methylesterification of HG in the culm-sieve element cell wall and a markedly reduced grain yield. The culm of Osqua2 mutant plants contains excessive sucrose (Suc), and a 13 CO2 feeding experiment showed that the Suc overaccumulation in the culm was caused by blocked Suc translocation. These and other findings demonstrate that OsQUA2 is essential for maintaining a high degree of methylesterification of HG in the rice culm-sieve element cell wall, which may be critical for efficient Suc partitioning and grain filling. In addition, our results suggest that the apoplastic pathway is involved in long-distance Suc transport in rice. The identification and characterization of the OsQUA2 gene and its functionality revealed a previously unknown contribution of HG methylesterification and provided insight into how modification of the cell wall regulates intercellular transport in plants.